2016
DOI: 10.7150/ijbs.16696
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Features of Vimentin-Containing Neural Precursor Cells in Olfactory Bulb of SOD1G93A Transgenic Mice: a Study about Resource of Endogenous Neural Stem Cells

Abstract: No any effective treatments can prevent from the motor neuron degeneration in amyotrophic lateral sclerosis (ALS) at present. In order to modulating the endogenous neural precursor cells (NPCs) to repairing the degenerative motor neurons in ALS, we studied the alteration of endogenous vimentin-containing NPCs in olfactory bulb (OB) at the different stages of SOD1 wlid-type and G93A transgenic mice. The results showed that the vimentin-containing cells (VCCs) were mainly distributed in the glomerular layer (Gl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 49 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…9,[16][17][18][19][20][21][22] Although the SVZ is the main source of OB interneurons, a number of studies claimed local NSCs exist in the adult rodent and human OB. [23][24][25][26][27][28][29][30][31] Furthermore, it has been reported that cells derived from the human OB give rise to neurons and glia in cell culture. [32][33][34][35][36][37] However, the precise location, features, and most importantly, the full neurogenic potential of these NSCs in vivo has yet to be defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[16][17][18][19][20][21][22] Although the SVZ is the main source of OB interneurons, a number of studies claimed local NSCs exist in the adult rodent and human OB. [23][24][25][26][27][28][29][30][31] Furthermore, it has been reported that cells derived from the human OB give rise to neurons and glia in cell culture. [32][33][34][35][36][37] However, the precise location, features, and most importantly, the full neurogenic potential of these NSCs in vivo has yet to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Although the SVZ is the main source of OB interneurons, a number of studies claimed local NSCs exist in the adult rodent and human OB 23‐31 . Furthermore, it has been reported that cells derived from the human OB give rise to neurons and glia in cell culture 32‐37 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that VCCs in the motor cortex, the olfactory cortex and the cingulate cortex significantly reduced and the number and density in the entire cerebrum didn't significantly increase. Previous studies reported that NPCs or NSCs in reduced regions of CNS migrated to damaged regions to restore neural cells at some pathological conditions 39, 40, 42, 52, 57. Therefore, we hypothesized that reduced VCCs in the motor cortex, the olfactory cortex and the cingulate cortex might migrate to other brain regions, and play a self-restoring ability to repair damaged neural cells in ALS-like Tg(SOD1*G93A)1Gur mice.…”
Section: Discussionmentioning
confidence: 91%
“…Current studies found that NPCs or NSCs in the brain and the spinal cord extensively proliferated, differentiated and migrated damaged regions to restore damaged neural cells at some pathological conditions such Parkinson's disease, Alzheimer's disease, spinal cord injury and ALS, partial NPCs or NSCs differentiated into astrocytes, oligodendrocytes and neuron cells, but the self-repair ability was very limited 39, 40, 42, 52, 57. However, in our study, the number and density of VCCs in the cerebrum of Tg(SOD1*G93A)1Gur mice weren't found to significantly increase at all stages of ALS-like Tg(SOD1*G93A)1Gur mice compared with WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…The vimentin-containing cells (VCCs) in CNS are potential resources of NPCs or NSCs [20][21][22][23][24][25]. The aim of this study was to investigate the potential modulation and mechanism of proliferation, differentiation, and migration of endogenous NPCs or NSCs in CNS at the ALS pathological condition by observing and analyzing the altered features of VCCs in the ALS-like Tg(SOD1*G93A)1Gur mice.…”
Section: Introductionmentioning
confidence: 99%